Tiny Tools - Measuring Change in Communities and Groups - Causemann, Bernward; Gohl, Eberhard; Brenner, Verena (Impact+, 2012)
Introduction to the Overview: Tiny Tools Why “Tiny Tools” for assessin g change? Currently, change is mostly assessed by NGO staff or externa l experts. The vision of this paper is that communities assess and ref lect change themselves and make use of that reflection with appropriat e tools. All the tools presented here are relatively quick and easy to learn (therefore “tiny”). With Tiny Tools we can assess change in one session. They can therefore be used where there are not baselines. Th ey are structured and systematic, and they are all widely tested: Expe rience shows that these tools lead to new insights, mobilise enthusias m and increase the capacity of communities to bring about further chan ge. The Tiny Tools are in line with what Participatory Rural Appraisal (PRA) wanted to achieve. Many are slight variations of PRA tools. For a detailed description of concepts, see the NGO-IDEAs Impact Toolbox (www.ngo-ideas.net/impact_toolbox) and the NGO-IDEAs Manual Self-Effec tiveness (www.ngo-ideas.net/monitoring_self_effectiveness). The tools are designed to visualise change, but also enable communities to refle ct on the reasons of change or verify assessments. They may be impleme nted once or continuously over time. We know that the time of communit y members is precious, and limited. Therefore all Tiny Tools can be pe rformed in a relatively short session, provided facilitators (it could be field staff or project officers) are experienced – and the communi ty knows and trusts them. The amount of time spent on the application of the tools may however be prolonged according to the needs of a comm unity or NGO. All of these tools are easy to learn for a facilitator e xperienced in participatory processes. Which tool should be introduced to which community? It is typically the decision of a development org anisation (or external experts) which tools they want to introduce int o a community. The staff need to assess which tool will lead to learni ng and action. It could also be that the staff realise aspects of chan ge that they do not understand well enough. These tools are good for e xploring change that we have not planned for and not anticipated. They are also good for exploring change in a context where we have no prio r information. Communities are the best experts for their situation, b ut we emphasise that the tools should be used in ways that benefit and empower the communities or individuals participating. The tool implem entations should lead to consequences on the grassroots as well as the NGO level. All Tiny Tools can be integrated into PIAR, the Analysis t ool in the NGO-IDEAs Impact Toolbox. Also, the Tiny Tools can help to prepare for the application of the Toolbox tools. They help to make pe ople aware of changes that can be observed. The following box gives so me hints how Tiny Tools relate to the Impact Toolbox tools, and to wha t extent they help to attribute change to development interventions.